2005
DOI: 10.1007/s00234-005-1428-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tumour type and distance on activation in the motor cortex

Abstract: Functional MRI has been widely used to identify the eloquent cortex in neurosurgical/radiosurgical planning and treatment of CNS neoplasms and malformations. In this study we examined the effect of CNS tumours on the blood oxygenation level-dependent (BOLD) activation maps in the primary and supplementary motor cortex. A total of 33 tumour patients and five healthy right-handed adults were enrolled in the study. Patients were divided into four groups based on tumour type and distance from primary motor cortex:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
16
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 19 publications
6
16
0
1
Order By: Relevance
“…These authors suggested that the effect on the signal intensity is due to a "stealing" of blood from the active region. These results are similar to those in previous studies from our laboratory 7 showing a significant effect of malignant tumors on the activation volume in the ipsilateral motor cortex during bilateral finger tapping; the effect also decreased with distance from the tumor.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These authors suggested that the effect on the signal intensity is due to a "stealing" of blood from the active region. These results are similar to those in previous studies from our laboratory 7 showing a significant effect of malignant tumors on the activation volume in the ipsilateral motor cortex during bilateral finger tapping; the effect also decreased with distance from the tumor.…”
Section: Discussionsupporting
confidence: 92%
“…5,6 The technique uses a gradient-echo imaging sequence with parameters sensitive to the oxygenation level in blood-that is, it reflects changes in the concentrations of oxy-and deoxyhemoglobin. We, 7 and others, 8,9 have used BOLD fMRI to map motor and other areas to spare eloquent cortex during surgery.…”
mentioning
confidence: 99%
“…Our findings seem to concur with the hypothesis that abnormal tumor neovasculature, a pathologic hallmark of GBMs, contributes to neurovascular uncoupling, which might lead to a decrease in BOLD functional MR imaging activation at the ipsilateral hemisphere (14,18,19,27). Yet, we draw attention to the fact that the significant interhemispheric difference in BOLD functional MR imaging activation observed in GBMs, but not within metastases and meningiomas, does not prove per se that there is a difference in this respect between the three tumor types.…”
Section: Neuroradiology: Influence Of Tumor Type and Bold Functional supporting
confidence: 90%
“…Previous smaller-scale studies have suggested that functional MR imaging activation volumes are truncated in the presence of tumors, particularly high-grade gliomas (15,16), thus making functional MR imaging potentially less reliable in peritumoral regions. It has been suggested that in addition to the histopathologic properties, other tumor properties (edema, volume, and location) and factors (prior brain surgery, age, motor deficits, and magnetic field strength) may influence BOLD functional MR imaging activation (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation